Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Alright, let's carefully analyze the steps and identify the error in the student's solution.
### Student's Original Equation:
[tex]\[2 \ln(x) = \ln(3x) - [\ln(9) - 2 \ln(3)]\][/tex]
First, let’s rewrite this by examining each part step-by-step.
### Step-by-Step Solution and Error Identification:
1. Starting Equation:
[tex]\[ 2 \ln(x) = \ln(3x) - [\ln(9) - 2 \ln(3)] \][/tex]
2. The student starts correctly by noting that:
[tex]\[ \ln \left(x^2 \right) = \ln (3x) - [\ln(9) - 2 \ln(3)] \][/tex]
3. Next, simplify [tex]\(\ln(9) - 2 \ln(3)\)[/tex]:
[tex]\[\ln(9) = \ln(3^2) = 2 \ln(3)\][/tex]
So:
[tex]\[\ln(9) - 2 \ln(3) = 2 \ln(3) - 2 \ln(3) = 0\][/tex]
4. Substituting this back into the equation results in:
[tex]\[\ln \left(x^2 \right) = \ln (3x) - 0\][/tex]
[tex]\[\ln \left(x^2 \right) = \ln (3x)\][/tex]
5. Up to this point, everything seems logically correct. However, the student introduces an erroneous step:
[tex]\[\ln (x^2) = \ln \left(\frac{3x}{0}\right)\][/tex]
This step is incorrect because there is no operation that introduces division by zero. The correct step should have been:
[tex]\[\ln \left(x^2\right) = \ln (3x)\][/tex]
6. To find the correct solution, let's use the correct approach:
[tex]\[\ln \left(x^2\right) = \ln (3x)\][/tex]
Since [tex]\(\ln(a) = \ln(b)\)[/tex] implies [tex]\(a = b\)[/tex], we get:
[tex]\[x^2 = 3x\][/tex]
7. Solving [tex]\(x^2 = 3x\)[/tex]:
[tex]\[x^2 - 3x = 0\][/tex]
[tex]\[x(x - 3) = 0\][/tex]
[tex]\[x = 0 \quad \text{or} \quad x = 3\][/tex]
Since [tex]\(x = 0\)[/tex] is not a valid solution in the context of logarithms (logarithm of zero is undefined), we discard this solution, leaving:
[tex]\[x = 3\][/tex]
### Correct Answer:
[tex]\[x = 3\][/tex]
### Detailed Solution Summary:
Inspecting the initial equation and ensuring each simplification step is accurate reveals that the student's final steps introduced division by zero, a clear error. Correct simplification and logical analysis yield the valid solution [tex]\(x = 3\)[/tex].
### Student's Original Equation:
[tex]\[2 \ln(x) = \ln(3x) - [\ln(9) - 2 \ln(3)]\][/tex]
First, let’s rewrite this by examining each part step-by-step.
### Step-by-Step Solution and Error Identification:
1. Starting Equation:
[tex]\[ 2 \ln(x) = \ln(3x) - [\ln(9) - 2 \ln(3)] \][/tex]
2. The student starts correctly by noting that:
[tex]\[ \ln \left(x^2 \right) = \ln (3x) - [\ln(9) - 2 \ln(3)] \][/tex]
3. Next, simplify [tex]\(\ln(9) - 2 \ln(3)\)[/tex]:
[tex]\[\ln(9) = \ln(3^2) = 2 \ln(3)\][/tex]
So:
[tex]\[\ln(9) - 2 \ln(3) = 2 \ln(3) - 2 \ln(3) = 0\][/tex]
4. Substituting this back into the equation results in:
[tex]\[\ln \left(x^2 \right) = \ln (3x) - 0\][/tex]
[tex]\[\ln \left(x^2 \right) = \ln (3x)\][/tex]
5. Up to this point, everything seems logically correct. However, the student introduces an erroneous step:
[tex]\[\ln (x^2) = \ln \left(\frac{3x}{0}\right)\][/tex]
This step is incorrect because there is no operation that introduces division by zero. The correct step should have been:
[tex]\[\ln \left(x^2\right) = \ln (3x)\][/tex]
6. To find the correct solution, let's use the correct approach:
[tex]\[\ln \left(x^2\right) = \ln (3x)\][/tex]
Since [tex]\(\ln(a) = \ln(b)\)[/tex] implies [tex]\(a = b\)[/tex], we get:
[tex]\[x^2 = 3x\][/tex]
7. Solving [tex]\(x^2 = 3x\)[/tex]:
[tex]\[x^2 - 3x = 0\][/tex]
[tex]\[x(x - 3) = 0\][/tex]
[tex]\[x = 0 \quad \text{or} \quad x = 3\][/tex]
Since [tex]\(x = 0\)[/tex] is not a valid solution in the context of logarithms (logarithm of zero is undefined), we discard this solution, leaving:
[tex]\[x = 3\][/tex]
### Correct Answer:
[tex]\[x = 3\][/tex]
### Detailed Solution Summary:
Inspecting the initial equation and ensuring each simplification step is accurate reveals that the student's final steps introduced division by zero, a clear error. Correct simplification and logical analysis yield the valid solution [tex]\(x = 3\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.